Effect of partially hydrolyzed guar gum on the composition and metabolic function of the intestinal flora of healthy mice. Issue 12 (4th November 2022) - Liu, Tong; Hu, Xuefei; Chen, Peng; Zhang, Renlingzi; Zhang, Shouqin; Chang, Wenjun; Wang, Junjie; Wang, Sheng
Abstract: Partially hydrolyzed guar gum (PHGG), a water‐soluble dietary fiber, has shown beneficial physiological effects in various disease models and is used as a prebiotic to regulate intestinal function. However, its role in healthy states remains unclear. The purpose of this study was to investigate the effects of PHGG on gut flora composition and predict metabolic function in healthy mice. Our study showed that PHGG supplementation had significant duration‐dependent effects on the composition and function of the intestinal flora of healthy mice. In specific, although the long‐term supplementation of PHGG may increase the abundance of some beneficial bacterial species and promote beneficial phenotypes, it may also cause increased body weight and decreased abundance and diversity of gut microorganisms. Therefore, the long‐term use of PHGG as a nutritional product still requires further investigation. Practical applications: As the importance of the gut microbiota has become more widely recognized, interventions that modulate the microbiome and its interaction with the host have gained much attention. While the capability of some prebiotics has largely been shown to have many beneficial effects, the evidence leaves much desirable, and microbiota regulation is explored differently in healthy or diseased states. Currently, the scientific community and regulatory authorities are beginning to pay attention to these unregulated and over‐the‐counter products claiming to possess probiotic and prebiotic properties. Studies exploring the rationality of these prebiotics as nutraceuticals for use in health states are essential. This study focuses on the effects of PHGG, a prebiotic, on intestinal flora, metabolism, and function when used in a healthy state over a long period. It is helpful to have a clearer understanding of the effect of PHGG on intestinal flora and the possible mechanisms of action to exert effects, which are indicative for the future application of PHGG as a nutraceutical or therapeutic agent.. Abstract : In healthy mice, long‐term addition of PHGG to the diet did not increase fecal concentrations of short‐chain fatty acids. However, it led to a decrease in alpha diversity and significantly altered the composition structure and metabolic function of the intestinal flora. In addition, the impact of PHGG on intestinal flora varied with the duration of addition.